ANALISIS UJARAN KEBENCIAN DI MEDIA SOSIAL (Twitter dan Instagram) TERHADAP CALON PRESIDEN REPUBLIK INDONESIA (RI) TAHUN 2024 - Fauzi Wirahyuda; Nursapia Harahap (CV. AFDIFAL MAJU BERKAH, 2024)
The closer it gets to the 2024 presidential election,the more political activities will be spread solely on social media to be seen and attract people's voting power towards each candidate for the 2024 presidential election. supporters of each opposing presidential candidate pair. This research aims to describe how hate speech behaves on social media (Twitter and Instagram) towards the 2024 Presidential Candidates of the Republic of Indonesia (RI). The research method used is a descriptive-analytic qualitative approach. The data analysis technique uses content analysis. The objects of this research are the respective candidates for President of the Republic of Indonesia in 2024, namely, Prabowo Subianto, Anies Rasyid Baswedan and Ganjar Pranowo. The results of the research are that there are still many individuals who still convey words or sentences of hate speech towards opposing candidates as a form of dislike for the presidential candidate. Many people use social networks (social media) but only a few know the aspects and impacts on legal regulations. Of course, in a situation like this, people need to be wise and alert in using social media so as not to get caught up in negative things that happen through social media. This is the reason for conducting this research empirically.